Modeling FinTech Variables in the Insurance Industry - Khorshidi, Arash; Sefati, Farid; Ghiyasvand, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The primary objective of this study is to model the impact of FinTech variables on the profitability of the insurance industry.Methodology: This study utilizes a sequential exploratory mixed-method approach. In the qualitative phase, data was collected through interviews with experts in the insurance and FinTech industries, along with a review of scientific literature. The data was analyzed using MAXQDA software to develop a qualitative model of FinTech variables affecting profitability. The second phase employed a quantitative approach, where developed tools were tested on a selected sample for validation and further analysis. The model was then evaluated based on qualitative and quantitative findings, with a causal loop diagram illustrating the interactions between key variables.Findings: The research identified three key FinTech-related variables: digital literacy, adoption of innovative technologies, and analysis and prediction. These variables form a positive feedback loop, enhancing digital and organizational empowerment. Findings show that FinTech adoption leads to increased operational efficiency, cost reduction, and improved risk assessment, which in turn boosts profitability for insurance companies. Additionally, collaboration with InsurTech startups and the integration of advanced technologies such as artificial intelligence (AI) and blockchain were found to be critical in maintaining competitive advantages and meeting evolving customer expectations.Conclusion: The study concludes that FinTech represents both a challenge and an opportunity for the insurance industry. Insurers must modernize their processes and adopt innovative technologies to remain competitive and responsive to market changes. The positive interaction between digital literacy, technological adoption, and market analysis strengthens the industry’s ability to enhance customer experience and profitability. Traditional insurance companies are encouraged to collaborate with FinTech and InsurTech startups, optimize business processes, and align with regulatory frameworks to effectively utilize FinTech innovations.